Macro and micro minerals: are frozen fruits a good source? - Spada,Patricia D.S. (2010)
Fruits are rich in minerals, which are essential for a wide variety of metabolic and physiologic processes in the human body. The use of frozen fruits has greatly spread in the last years not only in the preparation of juices, but also as raw material for yogurts, candies, cookies, cakes, ice creams, and children's food. However, up to now there is no data about the mineral profile of frozen fruits. This is the first database to quantify the levels of minerals in 23 samples of frozen fruits, including the most used around the world and some native fruits from the Amazon rainforest in Brazil. Considering the Dietary Reference Intakes, 100g of frozen fruits can provide 0.2 to 2.8% of macro and 2.5 to 100% of microminerals for adults (31-50 years old). Although geographical differences should be considered, these data can help to plan diets and to develop population interventions aiming to prevent chronic diseases.